2012
DOI: 10.1007/s00134-012-2535-y
|View full text |Cite
|
Sign up to set email alerts
|

Asynchrony, neural drive, ventilatory variability and COMFORT: NAVA versus pressure support in pediatric patients. A non-randomized cross-over trial

Abstract: Neurally adjusted ventilatory assist as compared to optimized PS results in improved synchrony, reduced ventilatory drive, increased breath-to-breath mechanical variability and improved patient comfort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
73
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 27 publications
11
73
0
3
Order By: Relevance
“…Additionally, this knowledge could be of major interest when comparing improved patient-ventilator synchrony documented with neurally adjusted ventilatory assist. 8,9 The purpose of this study was to investigate, using a bench model, the hypothesis that neonatal and/or adult ventilators equipped with neonatal/pediatric modes currently do not reliably administer pressure support (PS) in the absence or presence of air leaks.…”
Section: See the Related Editorial On Page 1606mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, this knowledge could be of major interest when comparing improved patient-ventilator synchrony documented with neurally adjusted ventilatory assist. 8,9 The purpose of this study was to investigate, using a bench model, the hypothesis that neonatal and/or adult ventilators equipped with neonatal/pediatric modes currently do not reliably administer pressure support (PS) in the absence or presence of air leaks.…”
Section: See the Related Editorial On Page 1606mentioning
confidence: 99%
“…However, in our bench test, the trigger delays measured for the Servo-i were in line with the values reported in clinical settings. 8,9,24 Pressurization. In the pediatric literature, there are a striking lack of data on the possible clinical impact of pressurization capacities of mechanical ventilators.…”
Section: Ventilation Performance In the Absence Of Leaksmentioning
confidence: 99%
“…Furthermore, the time of extubation always remains a challenging period for small patients after cardiac surgery, with some discomfort due to the increased work of breathing and the respiratory distress often present at this time. Previous studies suggest that improved synchronization by means of the EA di results in greater comfort for pediatric patients, 3 but synchronization alone cannot guarantee patient comfort. Bi-level ventilation can also lead to greater discomfort because of the increased gas flow through the nasal cannula during inspiratory periods.…”
Section: Discussionmentioning
confidence: 99%
“…2 Adult and pediatric studies showed that NAVA increases breath-to-breath variability and improves patient-ventilator synchrony and patient comfort. [3][4][5][6][7][8][9] This last improvement is also effective in NIV in adult and pediatric subjects 10,11 and in very low birthweight infants, even in the presence of large leaks. 12 To our knowledge, no previous study was designed to evaluate this ventilation mode exclusively in the postoperative period after cardiac surgery in newborns.…”
Section: Introductionmentioning
confidence: 97%
“…Both PAV and NAVA have been shown to reduce asynchrony compared with PSV. 18,19 We acknowledge that in very select populations of patients (eg, severe COPD, inappropriately small sized endotracheal tubes, morbid obesity), the approach to performing an SBT may have an impact on time to extubation. However, in a heterogeneous group of patients requiring ventilatory support, we would not expect the approach to an SBT to have an impact on time to extubation.…”
Section: See the Original Study On Page 1527mentioning
confidence: 99%